Light emitting diode epitaxial wafer and preparation method thereof, and light emitting diode
Patent Information
- Application Number
- CN202311411514.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-10-27
AI Technical Summary
[0002]目前GaN基蓝绿光LED外延结构中的P型层通常为Mg掺杂的GaN,这种常规的P型GaN层的Mg掺杂效率低、激活效率低,导致P型GaN层中的空穴浓度低
[0019]本发明提供的发光二极管外延片,P型层采用掺杂Mg的P型GaSb/P型GaN超晶格结构,P型GaSb/P型GaN超晶格结构产生的极化效应能显著提高Mg受主的电离,受主激活能更低,从而在相同的Mg掺杂浓度下能够产生更高的空穴浓度,增大了电子与空穴波函数的重叠率,从而提高量子阱中电子与空穴的辐射复合效率,最终提高LED的发光效率。
Smart Images

Figure CN117457826B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of semiconductor technology, and in particular to a light-emitting diode epitaxial wafer and its fabrication method, and a light-emitting diode. Background Technology
[0002] Currently, the P-type layer in the epitaxial structure of GaN-based blue-green LEDs is typically Mg-doped GaN. This conventional P-type GaN layer has low Mg doping efficiency and low activation efficiency, resulting in low hole concentration. To increase the hole concentration, a common method is to increase the Mg doping concentration; however, excessively high Mg doping concentration leads to a significant decrease in crystal quality. Alternatively, some researchers have proposed p-InGaN / AlGaN polarization doping to improve Mg doping efficiency using the polarization effect. However, the In composition in InGaN is extremely sensitive to growth temperature, which may lead to a decrease in crystal quality. In AlGaN, the high activation energy of doped Mg results in low activation efficiency; therefore, this method also struggles to balance crystal quality and doping efficiency. Summary of the Invention
[0003] The technical problem to be solved by the present invention is to provide an epitaxial wafer for a light-emitting diode that can improve the radiative recombination efficiency of electrons and holes in a quantum well, thereby improving the luminous efficiency of the light-emitting diode.
[0004] The technical problem to be solved by the present invention is to provide a method for preparing an epitaxial wafer of a light-emitting diode, which is simple in process and produces an epitaxial wafer with stable performance.
[0005] To achieve the above-mentioned technical effects, the present invention provides a light-emitting diode epitaxial wafer, including a substrate, and a buffer layer, an undoped GaN layer, an N-type GaN layer, a multiple quantum well layer, an electron blocking layer, a P-type layer and a P-type contact layer sequentially stacked on the substrate;
[0006] The P-type layer is a periodic structure formed by alternating layers of P-type GaSb layers and P-type GaN layers, with a period number ≥ 2.
[0007] As an improvement to the above technical solution, the thickness of the P-type GaSb layer is 2nm-5nm, and the thickness of the P-type GaN layer is 10nm-20nm.
[0008] As an improvement to the above technical solution, the thickness ratio of the P-type GaSb layer to the P-type GaN layer is 1:(3-5).
[0009] As an improvement to the above technical solution, the number of periods of the P-type layer is 2-5.
[0010] As an improvement to the above technical solution, the Mg doping concentration of the P-type layer is 1×10⁻⁶. 19 cm-3 -1×10 20 cm -3 .
[0011] As an improvement to the above technical solution, the electron blocking layer is an AlGaN electron blocking layer with an Al composition ratio of 0.1-0.5 and a thickness of 20nm-100nm.
[0012] Accordingly, the present invention also provides a method for preparing a GaN-based light-emitting diode epitaxial wafer, which includes the following steps:
[0013] A substrate is provided on which a buffer layer, an undoped GaN layer, an N-type GaN layer, a multiple quantum well layer, an electron blocking layer, a P-type layer and a P-type contact layer are sequentially grown.
[0014] The P-type layer is a periodic structure formed by alternating layers of P-type GaSb layers and P-type GaN layers, with a period number ≥ 2.
[0015] As an improvement to the above technical solution, the growth temperature of the P-type layer is 900℃-1000℃, and the growth pressure is 100Torr-600Torr.
[0016] As an improvement to the above technical solution, after the epitaxial structure is grown, it is annealed in an N2 atmosphere at a temperature of 650℃-850℃ for 5-15 minutes.
[0017] Accordingly, the present invention also provides a light-emitting diode, including the above-described light-emitting diode epitaxial wafer.
[0018] Implementing the embodiments of the present invention has the following beneficial effects:
[0019] The LED epitaxial wafer provided by this invention employs a Mg-doped P-type GaSb / P-type GaN superlattice structure in its P-type layer. The polarization effect generated by the P-type GaSb / P-type GaN superlattice structure can significantly improve the ionization of Mg acceptors, resulting in a lower acceptor activation energy. Consequently, a higher hole concentration can be generated at the same Mg doping concentration, increasing the overlap rate of electron and hole wave functions. This, in turn, improves the radiative recombination efficiency of electrons and holes in the quantum well, ultimately enhancing the luminous efficiency of the LED. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the structure of the light-emitting diode epitaxial wafer in an embodiment of the present invention;
[0021] Figure 2 This is a flowchart illustrating the fabrication method of the light-emitting diode epitaxial wafer in an embodiment of the present invention. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to specific embodiments.
[0023] like Figure 1 As shown, an embodiment of the present invention provides a GaN-based light-emitting diode epitaxial wafer, including a substrate 1, and a buffer layer 2, an undoped GaN layer 3, an N-type GaN layer 4, a multiple quantum well layer 5, an electron blocking layer 6, a P-type layer 7 and a P-type contact layer 8 sequentially stacked on the substrate 1.
[0024] The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers, with a period number ≥ 2. Setting the P-type layer as a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers can improve the doping efficiency of Mg in the P-type layer and increase the hole concentration. The band gap of GaSb is 0.73 eV, while that of GaN is 3.4 eV. The GaSb / GaN heterojunction forms a built-in polarized electric field. On one hand, the polarized electric field can generate a high concentration of two-dimensional hole gas, which can improve hole mobility and the radiative recombination efficiency of electrons and holes in the quantum well, ultimately improving the luminous efficiency of LEDs. On the other hand, the built-in polarized electric field tilts the valence band. Since Mg is located deep in GaN-based materials, more acceptor levels are below the Fermi level, which can greatly improve the ionization of Mg acceptors. The acceptor activation energy is low, which can generate a higher hole concentration and increase the overlap rate of electron and hole wave functions, thereby improving the radiative recombination efficiency of electrons and holes in the quantum well, and ultimately improving the luminous efficiency of LEDs.
[0025] In one embodiment, the thickness of the P-type GaSb layer is 2nm-5nm. For example, the thickness of the P-type GaSb layer is 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, or 5nm, but is not limited thereto. The thickness of the P-type GaN layer is 10nm-20nm. For example, the thickness of the P-type GaN layer is 10nm, 12nm, 14nm, 15nm, 16nm, 18nm, or 20nm, but is not limited thereto.
[0026] In one embodiment, the thickness ratio of the P-type GaSb layer to the P-type GaN layer is 1:(2-6). More preferably, the thickness ratio of the P-type GaSb layer to the P-type GaN layer is 1:(3-5); most preferably, the thickness ratio of the P-type GaSb layer to the P-type GaN layer is 1:5. By controlling the thickness ratio of the P-type GaSb layer to the P-type GaN layer, the crystal quality of each period composed of the P-type GaSb layer and the P-type GaN layer can be improved, thereby improving the quality of the P-type layer.
[0027] In one embodiment, the number of periods in the P-type layer is 2-5. The P-type layer composed of the P-type GaSb / P-type GaN superlattice structure of this invention can achieve excellent polarization effects with short-cycle growth. If the number of periods in the P-type layer is less than 2, it cannot provide a sufficient polarization electric field; if the number of periods in the P-type layer is greater than 5, it will result in a waste of resources.
[0028] In one embodiment, the Mg doping concentration of the P-type layer is 1 × 10⁻⁶. 19 cm -3 -1×10 20 cm -3 Within a certain range, the hole concentration in the P-type layer increases with the increase of the Mg doping concentration in the P-type layer. If the Mg doping concentration in the P-type layer is < 1 × 10⁻⁶, then... 19 cm -3 The P-type layer cannot provide enough holes; if the Mg doping concentration of the P-type layer is >1×10⁻⁶, the P-type layer will not be able to provide enough holes. 20 cm -3 This not only affects the crystal quality of the P-type layer but also reduces the hole concentration. Furthermore, excessively high doping concentrations are detrimental to improving antistatic properties. For example, the Mg doping concentration of the P-type layer is 1 × 10⁻⁶. 19 cm -3 2×10 19 cm -3 5×10 19 cm -3 7×10 19 cm -3 8×10 19 cm -3 Or 1×10 20 cm -3 However, it is not limited to this.
[0029] Correspondingly, the hole concentration of the P-type layer can be controlled to be 1×10⁻⁶. 17 cm -3 -1×10 28 cm -3 The low solubility and high compensation of Mg in GaN result in very low activation efficiency of Mg, with the carrier concentration typically only 0.1%-1% of the doping concentration. However, the superlattice P-type layer structure of this invention can increase the carrier concentration to 0.6%-1.8% of the Mg doping concentration, significantly improving the hole concentration at the same doping concentration.
[0030] Furthermore, since the p-type layer composed of p-type GaSb / p-type GaN superlattice increases the hole concentration, the thickness of the electron blocking layer and the proportion of Al in the electron blocking layer can be reduced accordingly, thereby further increasing the probability of holes entering the multi-quantum-well layer and improving the luminous efficiency. The electron blocking layer 6 is an AlGaN electron blocking layer with an Al content of 0.1-0.5% and a thickness of 20nm-100nm.
[0031] In addition to the composite interface layer described above, the other layered structures of the present invention have the following characteristics:
[0032] In one embodiment, the substrate 1 is one of a sapphire substrate, a silicon carbide substrate, or a silicon substrate. Preferably, the substrate 1 is a (0001) oriented sapphire substrate.
[0033] In one embodiment, the buffer layer 2 is an AlGaN buffer layer or an AlN buffer layer, and the thickness of the buffer layer 2 is 15nm-50nm. Preferably, the buffer layer 2 is an AlN buffer layer.
[0034] In one embodiment, the thickness of the undoped GaN layer 3 is 1 μm-3 μm.
[0035] In one embodiment, the N-type GaN layer 4 is Si-doped with a Si doping concentration of 1×10⁻⁶. 19 -1×10 20 cm -3 The thickness of the N-type GaN layer 4 is 1μm-3μm.
[0036] In one embodiment, the multi-quantum-well layer 5 includes periodically stacked InGaN quantum well layers and GaN quantum barrier layers with a period number of 6-12. The thickness of a single InGaN quantum well layer is 2nm-4nm, and the thickness of a single GaN quantum barrier layer is 8nm-20nm.
[0037] In one embodiment, the p-type contact layer 8 is a p-type GaN contact layer with a Mg doping concentration of 1×10⁻⁶. 19 -1×10 20 cm -3 The thickness of the P-type contact layer 8 is 10nm-50nm.
[0038] like Figure 2 As shown, this invention also discloses a method for fabricating a light-emitting diode epitaxial wafer, comprising the following steps:
[0039] S100 provides a substrate:
[0040] The substrate is selected as a sapphire substrate.
[0041] S200 growth buffer layer:
[0042] The reaction chamber temperature was controlled at 400℃-650℃, and the pressure at 150 Torr-500 Torr. NH3 was introduced to provide the N source, N2 was used as the carrier gas, and TMAl was introduced as the Al source. After the buffer layer was grown, in-situ annealing was performed under an H2 atmosphere at a temperature of 1000℃-1200℃, a pressure of 150 Torr-500 Torr, and a time of 5-10 minutes.
[0043] S300 growth of undoped GaN layer:
[0044] The reaction chamber temperature was controlled at 1050℃-1200℃, the pressure at 100Torr-500Torr, NH3 was introduced as the N source, N2 and H2 were used as carrier gases, and TMGa was introduced as the Ga source.
[0045] S400 growth of N-type GaN layers:
[0046] The reaction chamber temperature was controlled at 1100℃-1200℃, the pressure at 100Torr-300Torr, NH3 was introduced as the N source, N2 and H2 were introduced as the carrier gas, TMGa was introduced as the Ga source, and SiH4 was introduced as the N-type dopant.
[0047] S500 multi-quantum-well layer growth:
[0048] The reaction chamber temperature was controlled at 800℃-900℃ and the pressure at 100Torr-300Torr. NH3 was introduced as the N source, N2 as the carrier gas, TEGa was introduced as the Ga source, and TMIn was introduced as the In source to grow an InGaN quantum well layer. The reaction chamber temperature was controlled at 900℃-1000℃, the In source was turned off, N2 and H2 were used as carrier gases, and TEGa was introduced as the Ga source to grow a GaN quantum barrier layer. The InGaN quantum well layer and GaN quantum barrier layer were repeatedly stacked and periodically grown.
[0049] S600 electron blocking layer growth:
[0050] The reaction chamber temperature was controlled at 1000℃-1100℃, the pressure at 50Torr-100Torr, NH3 was introduced as the N source, N2 and H2 were introduced as the carrier gas, TMAl was introduced as the Al source, and TEGa was introduced as the Ga source.
[0051] S700 growth of P-type layers:
[0052] The reaction chamber temperature was controlled at 900℃-1000℃ and the pressure at 100Torr-600Torr. SbH3 was introduced as the Sb source, N2 and H2 were introduced as carrier gases, TEGa was introduced as the Ga source, and CP2Mg was introduced as the Mg source to grow a P-type GaSb layer. The Sb source was turned off, N2 and H2 were introduced as carrier gases, NH3 was introduced as the N source, TEGa was introduced as the Ga source, and CP2Mg was introduced as the Mg source to grow a P-type GaN layer. The P-type GaSb layer and the P-type GaN layer were repeatedly stacked and periodically grown.
[0053] S800 growth of P-type contact layer:
[0054] The reaction chamber temperature was controlled at 900℃-1000℃, the pressure at 100Torr-300Torr, NH3 was introduced as the N source, N2 and H2 were introduced as the carrier gas, TEGa was introduced as the Ga source, and CP2Mg was introduced as the P-type dopant.
[0055] S900 annealing treatment:
[0056] Annealing is performed in an N2 atmosphere at a temperature of 650℃-850℃ for 5-15 minutes.
[0057] The present invention will be further illustrated below with specific embodiments.
[0058] Example 1
[0059] This embodiment provides a light-emitting diode epitaxial wafer, including a substrate, and a buffer layer, an undoped GaN layer, an N-type GaN layer, a multiple quantum well layer, an electron blocking layer, a P-type layer and a P-type contact layer sequentially stacked on the substrate.
[0060] The substrate is a sapphire substrate.
[0061] The buffer layer is an AlN buffer layer with a thickness of 30nm.
[0062] The thickness of the undoped GaN layer is 400 nm.
[0063] The Si doping concentration in the N-type GaN layer is 7 × 10⁻⁶. 18 cm -3 The thickness is 2μm.
[0064] The multi-quantum-well layer consists of periodically alternating InGaN quantum well layers and GaN quantum barrier layers, with a period number of 5. The InGaN quantum well layer has a thickness of 3 nm, and the GaN quantum barrier layer has a thickness of 10 nm.
[0065] The electron blocking layer is Al 0.25 Ga 0.75 The N-electron blocking layer has a thickness of 3 nm.
[0066] The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN, with a period number of 3. The thickness of the P-type GaSb layer is 2 nm, the thickness of the P-type GaN layer is 12 nm, and the Mg doping concentration of the P-type layer is 1 × 10⁻⁶. 19 cm -3 .
[0067] The P-type contact layer is a P-type GaN contact layer, with a Mg doping concentration of 1×10⁻⁶. 17 cm -3 The thickness is 10nm.
[0068] The above-mentioned method for fabricating an epitaxial wafer of a light-emitting diode includes the following steps:
[0069] S100 provides a substrate:
[0070] (0001) crystal orientation sapphire substrate is selected.
[0071] S200 growth buffer layer:
[0072] The reaction chamber temperature was controlled at 500℃ and the pressure at 200 Torr. NH3 was introduced to provide the N source, N2 was used as the carrier gas, TMGa was introduced as the Ga source, and TMAl was introduced as the Al source. After the buffer layer was grown, in-situ annealing was performed under an H2 atmosphere at a temperature of 1100℃, a pressure of 200 Torr, and a time of 8 min.
[0073] S300 growth of undoped GaN layer:
[0074] The reaction chamber temperature was controlled at 1100℃ and the pressure at 200 Torr. NH3 was introduced as the N source, N2 and H2 were used as carrier gases, and TMGa was introduced as the Ga source.
[0075] S400 growth of N-type GaN layers:
[0076] The reaction chamber temperature was controlled at 1150℃ and the pressure at 220 Torr. NH3 was introduced as the N source, N2 and H2 were introduced as carrier gases, TMGa was introduced as the Ga source, and SiH4 was introduced as the N-type dopant.
[0077] S500 multi-quantum-well layer growth:
[0078] The reaction chamber temperature was controlled at 850℃ and the pressure at 200 Torr. NH3 was introduced as the N source, N2 as the carrier gas, TEGa was introduced as the Ga source, and TMIn was introduced as the In source to grow an InGaN quantum well layer. The reaction chamber temperature was controlled at 950℃, the In source was turned off, N2 and H2 were used as carrier gases, and TEGa was introduced as the Ga source to grow a GaN quantum barrier layer. The InGaN quantum well layer and GaN quantum barrier layer were repeatedly stacked and periodically grown.
[0079] S600 electron blocking layer growth:
[0080] The reaction chamber temperature was controlled at 1050℃ and the pressure at 80 Torr. NH3 was introduced as the N source, N2 and H2 were introduced as carrier gases, TMAl was introduced as the Al source, and TEGa was introduced as the Ga source.
[0081] S700 growth of P-type layers:
[0082] The reaction chamber temperature was controlled at 950℃ and the pressure at 200 Torr. SbH3 was introduced as the Sb source, N2 and H2 were introduced as carrier gases, TEGa was introduced as the Ga source, and CP2Mg was introduced as the Mg source to grow a P-type GaSb layer. The Sb source was turned off, N2 and H2 were introduced as carrier gases, NH3 was introduced as the N source, TEGa was introduced as the Ga source, and CP2Mg was introduced as the Mg source to grow a P-type GaN layer. The P-type GaSb layer and the P-type GaN layer were repeatedly stacked and periodically grown.
[0083] S800 growth of P-type contact layer:
[0084] The reaction chamber temperature was controlled at 950℃ and the pressure at 150 Torr. NH3 was introduced as the N source, N2 and H2 were introduced as carrier gases, TEGa was introduced as the Ga source, and CP2Mg was introduced as the P-type dopant.
[0085] S900 annealing treatment:
[0086] Annealing was performed in an N2 atmosphere at a temperature of 700°C for 8 minutes.
[0087] Example 2
[0088] This embodiment provides a light-emitting diode epitaxial wafer. The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers, with a period number of 3. The thickness of the P-type GaSb layer is 3 nm, the thickness of the P-type GaN layer is 12 nm, and the Mg doping concentration of the P-type layer is 1 × 10⁻⁶. 19 cm -3 The rest is the same as in Example 1.
[0089] Example 3
[0090] This embodiment provides a light-emitting diode epitaxial wafer. The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers, with a period number of 3. The thickness of the P-type GaSb layer is 4 nm, the thickness of the P-type GaN layer is 12 nm, and the Mg doping concentration of the P-type layer is 1 × 10⁻⁶. 19 cm -3 The rest is the same as in Example 1.
[0091] Example 4
[0092] This embodiment provides a light-emitting diode epitaxial wafer. The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers, with a period number of 3. The thickness of the P-type GaSb layer is 5 nm, the thickness of the P-type GaN layer is 12 nm, and the Mg doping concentration of the P-type layer is 1 × 10⁻⁶. 19 cm -33 The rest is the same as in Example 1.
[0093] Example 5
[0094] This embodiment provides a light-emitting diode epitaxial wafer. The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers, with a period number of 3. The thickness of the P-type GaSb layer is 3 nm, the thickness of the P-type GaN layer is 15 nm, and the Mg doping concentration of the P-type layer is 1 × 10⁻⁶. 19 cm -3 The rest is the same as in Example 1.
[0095] Example 6
[0096] This embodiment provides a light-emitting diode epitaxial wafer. The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers, with a period number of 3. The thickness of the P-type GaSb layer is 3 nm, the thickness of the P-type GaN layer is 18 nm, and the Mg doping concentration of the P-type layer is 1 × 10⁻⁶. 19 cm -3 The rest is the same as in Example 1.
[0097] Example 7
[0098] This embodiment provides a light-emitting diode epitaxial wafer. The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers, with a period number of 3. The thickness of the P-type GaSb layer is 3 nm, the thickness of the P-type GaN layer is 15 nm, and the Mg doping concentration of the P-type layer is 3 × 10⁻⁶. 19 cm -3 The rest is the same as in Example 1.
[0099] Example 8
[0100] This embodiment provides a light-emitting diode epitaxial wafer. The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers, with a period number of 3. The thickness of the P-type GaSb layer is 3 nm, the thickness of the P-type GaN layer is 15 nm, and the Mg doping concentration of the P-type layer is 5 × 10⁻⁶. 19 cm -3 The rest is the same as in Example 1.
[0101] Example 9
[0102] This embodiment provides a light-emitting diode epitaxial wafer. The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers, with a period number of 3. The thickness of the P-type GaSb layer is 3 nm, the thickness of the P-type GaN layer is 15 nm, and the Mg doping concentration of the P-type layer is 7 × 10⁻⁶. 19 cm -3 The rest is the same as in Example 1.
[0103] Example 10
[0104] This embodiment provides a light-emitting diode epitaxial wafer. The P-type layer is a periodic structure formed by alternating layers of P-type GaSb and P-type GaN layers, with a period number of 3. The thickness of the P-type GaSb layer is 3 nm, the thickness of the P-type GaN layer is 15 nm, and the Mg doping concentration of the P-type layer is 9 × 10⁻⁶. 19 cm -3 The rest is the same as in Example 1.
[0105] Comparative Example 1
[0106] This comparative example provides a light-emitting diode epitaxial wafer, which differs from Example 1 in that the P-type layer is a conventional Mg-doped P-type GaN layer, and the Mg doping concentration is 1×10⁻⁶. 19 cm -3 The corresponding preparation method does not include the preparation of P-type GaSb / P-type GaN layers; the rest is the same as in Example 1.
[0107] Performance testing:
[0108] LED chips with an emission wavelength of 455nm and a size of 10mil × 25mil were fabricated from the epitaxial wafers of light-emitting diodes prepared in Examples 1-10 and Comparative Example 1. Their luminous intensity (120mA), operating voltage, and antistatic performance (-6kV) were tested. The test results are shown in Table 1.
[0109] Table 1. Photoelectric performance test results of LED epitaxial wafers
[0110]
[0111]
[0112] As can be seen from the comparison between Examples 1-10 and Comparative Example 1, the chip made from the epitaxial wafer of the light-emitting diode provided by the present invention can reduce the operating voltage while improving the light-emitting brightness, and has good anti-static performance.
[0113] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A light-emitting diode epitaxial wafer, characterized in that, It includes a substrate, and a buffer layer, an undoped GaN layer, an N-type GaN layer, a multiple quantum well layer, an electron blocking layer, a P-type layer and a P-type contact layer sequentially stacked on the substrate; The P-type layer is a periodic structure formed by alternating layers of P-type GaSb layers and P-type GaN layers, with a period number ≥ 2; The thickness of the P-type GaSb layer is 2nm-5nm, and the thickness of the P-type GaN layer is 10nm-20nm; The Mg doping concentration of the P-type layer is 1×10⁻⁶. 19 cm -3 -1×10 20 cm -3 .
2. The light-emitting diode epitaxial wafer as described in claim 1, characterized in that, The thickness ratio of the P-type GaSb layer to the P-type GaN layer is 1:(3-5).
3. The light-emitting diode epitaxial wafer as described in claim 1, characterized in that, The number of periods in the P-type layer is 2-5.
4. The light-emitting diode epitaxial wafer as described in claim 1, characterized in that, The electron blocking layer is an AlGaN electron blocking layer with an Al composition ratio of 0.1-0.5 and a thickness of 20nm-100nm.
5. A method for fabricating a light-emitting diode epitaxial wafer, used to fabricate a light-emitting diode epitaxial wafer as described in any one of claims 1-4, characterized in that, Includes the following steps: A substrate is provided on which a buffer layer, an undoped GaN layer, an N-type GaN layer, a multiple quantum well layer, an electron blocking layer, a P-type layer and a P-type contact layer are sequentially grown. The P-type layer is a periodic structure formed by alternating layers of P-type GaSb layers and P-type GaN layers, with a period number ≥ 2.
6. The method for fabricating a light-emitting diode epitaxial wafer as described in claim 5, characterized in that, The growth temperature of the P-type layer is 900℃-1000℃, and the growth pressure is 100Torr-600Torr.
7. The method for fabricating a light-emitting diode epitaxial wafer as described in claim 5, characterized in that, After the epitaxial wafer structure is grown, it is annealed in an N2 atmosphere at a temperature of 650℃-850℃ for 5-15 minutes.
8. A light-emitting diode, characterized in that, The light-emitting diode includes a light-emitting diode epitaxial wafer as described in any one of claims 1-4.
Citation Information
Patent Citations
Method of manufacturing semiconductor device
CN102208496A
Method for manufacturing optical semiconductor element
JP2021027083A